ANALYSIS OF THE EFFECT OF WCTO, FATO AND TA ON COMPANY VALUE WITH ROE AS INTERVENING VARIABLES - Bambang Widagdo; Chalimatuz Sa'diyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The aims of this research is to examine the direct effect and indirect effect of Working Capital Turnover, Fix Asset Turnover and Total Asset on Firm Value with Return On Equity as an intervening variable. This research sample is manufacturing companies listed in the Indonesia Stock Exchange (IDX) for the period 2017-2019 by using purposive sampling method. There are 109 manufacturing companies selected as sample. The analysis used is Partial Least Square Analysis. The result of direct effect showed that WCTO has positive significant effect on Firm Value. WCTO has a positive significant effect on ROE. FATO has a positive significant effect on ROE. TA has a positive significant effect on ROE. TA has a positive significant effect on Firm Value. ROE has a positive significant effect on Firm Value. The result of indirect effect showed that WCTO, FATO and TA influence Firm Value through ROE. Besides, it was found that the greatest of indirect effect showed that FATO influence Firm Value through ROE. Keywords: Working Capital Turnover, Fix Asset Turnover; Total Asset; Firm Value